Teaching art via digital technology for the elderly applying with inclusive design: A review - Kittichai Kasemsarn; Antika Sawadsri (Journal of Infrastructure Policy and Development, 2024)
Art studies and activities for older adults have received significantly less attention as a result of prohibitively expensive materials that are unfit for commercial use, and research utilizing digital technology to investigate artistic activities for older adults is extremely limited. The purpose of this article is to analyze and review recent research in these fields to summarize the current trends. The literature review comprised 108 articles from databases that included Scopus, ScienceDirect, and Google Scholar. The papers were subjected to a thorough examination by the VOSviewer program and researchers, who utilized content analysis to classify them into four themes: 1) inclusive design; 2) accessibility; 3) digital art therapy and 4) digital technology environments. Further investigation and development are necessary to propose a novel approach to instructing senior-level art utilizing cutting-edge technologies, which could be enhanced by the findings of this review article.
Keywords: Technology Use by Older Adults